Development and validation of an ultraviolet-visible spectrophotometric method for quantifying oxytetracycline for veterinary use - Kaluka Tshibamba, Jacques Mbuyi; Kakumba, Jocelyn Mankulu; Mabaya, Timothy Mavanga; Djang’ieng’a, Roland Marini; Kindenge, Jérémie Mbinze (Frontiers in Analytical Science, 2023)
In sub-Saharan Africa, breeding plays a key role because it is an important source of highly valued protein in the human diet, also because it is an essential driver for socio-economic development in view of its multiple roles. It represents a form of investment and is also important from a socio-cultural point of view (ceremonies, social position, etc.). Livestock is an important source of income, livelihoods, nutrition and food security. However, this breeding is confronted, among other things, with major sanitary constraints which disturb the real expression of its performance. Furthermore, the circulation of non-compliant antibiotics on the market constitutes a major threat to animal health, public health and the environment. This research aimed to develop and validate a UV-vis method for the quantification of Oxytetracycline in pharmaceutical forms. The developed method was validated following the total error strategy having as decision tool the accuracy profile. After its completion, The method showed a good trueness expressed in terms of absolute and relative bias and comprised within the tolerate interval of [-2%, +2%]. The method had also a good precision expressed in terms of repeatability and intermediate precision, which had respectively values lower than 2% and 4%; we also assessed the recovery and accuracy of the method that showed results fitting with the specification limits. After its validation, the method was applied for quantification in 47 Oxytetracycline injectable samples where we obtained 28 samples complying with specifications and 19 out of specification samples. That led us to conclude, the developed method was really validated and appropriated for quantification in terms of routine quality control of Oxytetracycline injection. For other pharmaceutical presentations, the method needs to be reviewed and revalidated accordingly.